Obesity Increases Time to Union in Surgically Treated Pediatric Fracture Patients. (5th January 2022) - Heath, David; Momtaz, David; Ghali, Abdullah; Salazar, Luis; Gibbons, Steven; Hogue, Grant
Abstract : Introduction: To determine whether obesity affects time to radiographic union in surgically treated pediatric extremity fractures. Methods: A retrospective review of pediatric patients with extremity fractures at a Level 1 trauma center from 2010 to 2020. Those treated conservatively and patients with nonunions were excluded. Union was defined as radiographic evidence of bridging callus on all sides of the fracture and absence of the previous fracture line. Results: Obese patients had a markedly increased time to union when compared with others, even when age, sex, fracture type, race, and ethnicity were controlled for. The mean time to union for obese and nonobese patients were 152 and 93.59 days, respectively ( P < 0.001). Obese patients had 3.39 times increased odds of having increased time to union. Obese patients had 6.64 times increased odds of having fractures with delayed union of 4 months or greater ( P < 0.001). Conclusions: There is a positive correlation between obesity and time to union in surgically treated pediatric fracture patients.